Between Extraordinary and Marginalized: Negotiating Tensions in Becoming Special Education-Certified Teachers. Issue 4 (2nd October 2018) - Roegman, Rachel; Pratt, Suzanne; Sanchez, Sabrina; Chen, Crystal
ABSTRACT: The field of special education is in flux, with high shortages and attrition and increasing requirements around quality teachers and teaching contexts. In this study, we explore how preservice teachers develop identities as special education-certified teachers within this context. Data include focus groups, admissions essays, and class assignments from 3 years of a masters-level preparation program. Analysis began with open coding, and initial themes included positioning, power, and marginalization. Iterative analysis led to findings around negotiation—how preservice teachers negotiated what it meant to be a teacher in diverse teaching contexts while both maintaining a view of special education-certified teachers as extraordinary and also experiencing marginalization within their roles. Implications include supporting teacher candidates in managing these tensions, as well as a need for programs to partner with schools as a whole and not just individual cooperating teachers.